'Land Complaints' in Bizana, c.1940-1963: Living Customary Law in an Administrative Archive - Fay, Derick A. (Journal of southern African studies, 2021)
The 'land complaints' files of the Transkei magistrates from the mid 20th century provide an under-recognised and important source regarding living customary law in South Africa. Land complaints were treated as 'purely administrative' rather than legal matters and hence not subject to appeals outside the Native Affairs Department, creating disincentives and obstacles to bringing claims grounded in living practice into fora where they might challenge official regulations and be 'ascertained' as customary law. Nevertheless, these sources reveal disputes, norms and practices that have not been recognised in official customary law, the administrative regulations governing land in the region or the post-apartheid jurisprudence on living customary law. I examine cases from the culturally conservative district of Bizana, in the north-eastern coastal Transkei, to highlight four issues: first, unmarried men could claim, acquire and maintain land rights; second, land would not revert to the headman for reallocation if its owner died or left the area; third, lending and sale of land took place, often without the approval of the headman; fourth, location boundaries were inconsistently followed as landholding cut across the boundaries used by administrators.